Influence of printing parameters and short carbon fibre reinforcement on fatigue behaviour, dimensional accuracy and macrogeometrical deviations of polylactic acid in material extrusion - Bermudo-Gamboa, Carolina; Martín-Béjar, Sergio; Trujillo-Vilches, Francisco Javier; Sevilla-Hurtado, Lorenzo (Elsevier, 2023)
This paper evaluates the potential of short carbon fibres as a reinforcement material in order to improve the fatigue resistance of PLA. The fatigue behaviour has been analysed through rotational bending fatigue tests. The influence of printing parameters, such as layer thickness, printing temperature and printing speed, on the mechanical behaviour, dimensional accuracy and macrogeometrical deviations of printed parts have also been analysed as they can too interfere with the mechanical behaviour of the parts. The results show that there is no improvement on the mechanical behaviour of the printed parts with the incorporation of short carbon fibres. On the contrary, the fatigue behaviour worsens due to the poor adhesion between the short carbon fibres and the PLA matrix. Fatigue life is reduced by 6% compared to PLA. Focusing only on the printing parameters, it is shown that at the highest temperature allowed, the fatigue behaviour improves a 12%. The Printing speed is the least influential variable, with the layer thickness having the greatest influence, increasing fatigue life by 15% comparing 0.1 mm and 0.3 mm. Therefore, the best combination would be to print with the highest temperature and the highest layer thickness, for this case study. Finally, a parametric relationship is presented in order to relate the layer thickness with the fatigue behaviour.Fundi
Keywords: Extrusión (Mecánica); Fibras de carbono; Materiales - Fatiga; Procesos de fabricación; Additive manufacturing; Polylactic acid; Short carbon fibres; Material extrusion; Printing parameters; Fatigue behaviour; Dimensional accuracy; Impresión 3D